The Position of Teachers in Contemporary Education Pedagogical Studies Q.S Al-Mujadilah Verse 11 - Ilmi, Tyara Azky Nurul; Salim, Hakimuddin (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This article examines the position of teachers in contemporary education through a pedagogical study of the content of Qur’anic Surah Al-Mujādilah (58) verse 11. The purpose of this study is to analyze the characteristics and challenges of contemporary education, to examine the position of teachers in both national and international contexts, and to reveal the Qur’anic pedagogical foundations concerning teachers’ dignity and justice. This research employs a qualitative approach based on library research using the pedagogical exegesis method (Tafsir Tarbawi), focusing on conceptual and normative analysis of the Qur’anic text as well as scholarly literature on contemporary education and teacher professionalism. The findings indicate that contemporary education is characterized by the dominance of instrumental rationality, the standardization of educational systems, and increasing professional demands on teachers that are not always accompanied by social recognition and structural justice. This condition creates a gap between the professionalism expected of teachers and the social status they receive. Qur’anic Surah Al-Mujādilah (58) verse 11 provides a pedagogical foundation that emphasizes the elevation of rank based on faith and knowledge; therefore, dignity, moral integrity, and social justice become fundamental principles in understanding teacher professionalism. This study affirms that the Qur’anic perspective offers a relevant value framework for reaffirming the dignity of teachers within contemporary educational systems.